SUFISTIC APPROACH IN ISLAMIC EDUCATION TO INCREASE SOCIAL CONCERN AND PEACE - Siregar, Eliana; Susilawati, Susilawati; Arrasyid, Arrasyid (State Islamic University North Sumatra, 2024)
Conflict becomes part of contemporary phenomena that embraces all dimensions of human life, starting from the level of individuals, society, to relations between countries. Conflict in all of its variety, both economic, political conflicts, even conflicts between civilizations, cannot be separated from the “on-name” religion. Islam which teaches love and peace is distorted into Islam that teaches conflict. Islamic education in a broad context is responsible for the formation of logical thinking of humans who like to spread terror and conflict. This paper examines how the Sufism approach in Islamic education plays its part as the Islamic tradition that teaches Islam in the form of love and spreads Peaceful Islam and has A peace of mind with research Library research that uses qualitative descriptive analysis techniques with the results of research that is mystical approach in Islamic education fundamental alternatives in order to reduce conflict and bring peace.